Benevolent Sexism and Women Agency in Play Diving for Pearls (2012) by Katherine Thomson - Nilam Chris Monica; Muhd. Al-Hafizh (Universitas Negeri Padang, 2023)
This thesis is an analysis of a play written by Katherine Thomson entitled Diving for Pearls (2012). This analysis looks at benevolent sexism that is experienced by women who are victims of benevolent sexism acts. And also shows the actions of women's agency carried out by women to get out of the limited space they receive in their environment and also to be able to change their lives for the better. This analysis related to the feminist approach and the concept of benevolent sexism by Glick and Fiske and women agency by Buttler. The aim of this analysis is to what extent the character, conflict (plot), setting and stage direction contribute to reveal the issue of benevolent sexism and women agency. This analysis also depends a lot on the narrator to determine which parts of the play are used as the data. The result of the study shows that the woman experienced benevolent sexism such as always being considered weak, unable to take responsibility for herself, unable to protect herself and must always be protected, and not solving her own problems. However, Barbara shows the desire and belief that she has rights and is able to change her life for the better with her own abilities.